RISK EXPOSURE DURING THE GLOBAL FINANCIAL CRISIS, THE CASE OF ISLAMIC BANKS EVIDENCE FROM INDONESIA - Syahruddin Syahruddin (Ijtihad, 2012)
This study aims to examine the way Islamic financial institutions dealt with the recent financial problems in term of risk management. In total, three Islamic banks and the same number of conventional banks selected from the country werw analyzed. The capital ratios, based on the Basal Committee, are the primary tools used to analyze the riskiness of the Islamic and conventional banks. Capital ratios are considered as areliable source in predicting potential bankruptcies. The study documents that Islamic banks are maintaining better capital ratios than to their conventional counterparts. The study presensts a new approach to the comparative performance of Islamic and conventional banks in terms of risk management. The findings can be very useful to academicians anf banking professional alike.